Contribution of individual Ebp Pilus subunits of Enterococcus faecalis OG1RF to pilus biogenesis, biofilm formation and urinary tract infection. - Jouko Sillanpää; Chungyu Chang; Kavindra V Singh; Maria Camila Montealegre; Sreedhar R Nallapareddy; Barrett R Harvey; Hung Ton-That; Barbara E Murray (PLoS ONE, 2013)
The endocarditis and biofilm-associated pilus (Ebp) operon is a component of the core genome of Enterococcus faecalis that has been shown to be important for biofilm formation, adherence to host fibrinogen, collagen and platelets, and in experimental endocarditis and urinary tract infection models. Here, we created single and double deletion mutants of the pilus subunits and sortases; next, by combining western blotting, immunoelectron microscopy, and using ebpR in trans to increase pilus production, we identified EbpA as the tip pilin and EbpB as anchor at the pilus base, the latter attached to cell wall by the housekeeping sortase, SrtA. We also confirmed EbpC and Bps as the major pilin and pilin-specific sortase, respectively, both required for pilus polymerization. Interestingly, pilus length was increased and the number of pili decreased by deleting ebpA, while control overexpression of ebpA in trans restored wild-type levels, suggesting a dual role for EbpA in both initiation and termination of pilus polymerization. We next investigated the contribution of each pilin subunit to biofilm formation and UTI. Significant reduction in biofilm formation was observed with deletion of ebpA or ebpC (P<0.001) while ebpB was found to be dispensable; a similar result was seen in kidney CFUs in experimental UTI (ΔebpA, ΔebpC, P≤0.0093; ΔebpB, non-significant, each vs. OG1RF). Hence, our data provide important structural and functional information about these ubiquitous E. faecalis pili and, based on their demonstrated importance in biofilm and infection, suggest EbpA and EbpC as potential targets for antibody-based therapeutic approaches.